Participaç\~ao, buzzwords e poder: Uma análise crítica da tendência de proliferaç\~ao de conselhos e comitês locais enquanto instrumentos de gest\~ao ambiente no Brasil - Igor Ferraz da Fonseca (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article examines the use and dissemination of the concept of participation in environmental and development policies, focusing on implementation of local councils in Brazil - especially those linked to socio-environmental issues. The hypothesis advanced here is that the current use of the concept of participation is typical of a buzzword, being rhetorically successful while its implementation often fail. The findings highlight that the several failures and obstacles faced by participatory councils in Brazil could be decreased if the singularities of the local contexts were considered for the establishment of institutions aimed at promoting citizenship, social control and accountability in public policies. Thus, the analysis of power relations, socioeconomic structures of larger scale and greater methodological flexibility are important elements for increase the efficiency and effectiveness of these councils.
Keywords: H83; Q01; Y80; 330; Umweltpolitik; Partizipation; Bürgerbeteiligung; Brasilien